(untitled) (Journal of Atomic and Molecular Sciences, 2010)
5-fluoro-1-(tetrahydrofuran-2-yl)pyrimidine-2,4(1H,3H)-dione also known as tegafur, is an important component of Tegafur-uracil (UFUR), a chemotherapy drug used in the treatment of cancer. The equilibrium geometries of "Tegafur" and 5-fluoro-uracil (5-FU) have been determined and analyzed at DFT level employing the basis set 6-311+G(d, p). The molecular electrostatic potential surface which displays the activity centres of a molecule, has been used along with frontier orbital energy gap, electric moments, first static hyperpolarizability, to interpret the better selectivity of prodrug tegafur over the drug 5-FU. The harmonic frequencies of prodrug tegafur have also been calculated to understand its complete vibrational dynamics. In general, a good agreement between experimental and calculated normal modes of vibrations has been observed.